Empowering Women by Strengthening the Economic Sector and Digital Marketing Through a Women's School in Tambakmenjangan Village - Erlangga, Fajar Sukma; Susilowati , Dwi; Santoso, Moh.Heru Budi (LPPPM STAI Darul Hikmah Bangkalan, 2024)
The COVID-19 pandemic has had a significant impact on various sectors, including tourism, trade and industry, particularly impacting micro, small and medium enterprises (MSMEs) in Indonesia. According to Adistianingsih and Panjaitan (2022), Indonesia ranks 109th out of 144 countries in terms of women's participation in the economy and entrepreneurial opportunities. This reflects the limited opportunities for women in the world of work and entrepreneurship in Indonesia. Patriarchal culture and negative stigma surrounding the role of women in rural areas exacerbate this problem. This program aims to overcome the low economic participation of women in Tambakmenjangan Village, Lamongan Regency. The problem is the low level of women's empowerment, which has an impact on low levels of education, societal stigma and early marriage. This program utilizes non-formal education and skills training programs for women which are carried out in collaboration with the Lamongan Islamic University student organization. The activity design includes a six-month culinary, fashion and make-up training program for women in Tambakmenjangan Village. The findings show that this program has succeeded in empowering women by increasing their skills and knowledge in various fields. The program also involves partnerships with government agencies, local businesses, and educational institutions. Monitoring and evaluation were carried out to ensure program effectiveness, and workshops were held to disseminate and publicize the results. The implications of this research are very significant because they contribute to the empowerment of women in rural areas and address the gender gap in economic participation.